2013
DOI: 10.1016/j.pediatrneurol.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors for Perinatal Arterial Ischemic Stroke

Abstract: The cause of perinatal arterial ischemic stroke is unknown in most cases. We explored whether genetic polymorphisms modify the risk of perinatal arterial ischemic stroke. In a population-based case-control study of 1997–2002 births at Kaiser Permanente Northern California, we identified 13 white infants with perinatal arterial ischemic stroke. Controls included 86 randomly selected white infants. We genotyped polymorphisms in 9 genes involved in inflammation, thrombosis or lipid metabolism that have been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…Figure 1 shows the results of literature search and selection. A total of 186 articles were retrieved with the comprehensive literature search, and finally 25 articles (Bai and Cheng 2004;Balding et al 2004;Lee et al 2004;Um and Kim 2004;Karahan et al 2005;Rubattu et al 2005;Harcos et al 2006;Lalouschek et al 2006;Llamas Sillero et al 2007;Zhang et al 2007;Liu et al 2009Liu et al , 2012Shi et al 2009;Kim et al 2010;Tong et al 2010;Markoula et al 2011;Munshi et al 2011;Sultana et al 2011;Szabo and Acsady 2011;Wu et al 2011;Cui et al 2012;Tuttolomondo et al 2012;Gelfand et al 2013;Ma 2012) (18 in English and seven in Chinese) of them were included in the present study according to the eligible criteria. Forty-nine eligible case-control studies from these 25 articles involve 23 studies of -308G/A (6220 patients and 6531 controls), 14 studies of -238G/A (4760 patients and 4389 controls), four studies of -857C/T (2589 patients and 2097 controls), three studies of -1031T/C (2416 patients and 1948 controls), one study (404 patients and 415 controls) of -244G/ A and -367G/A, one study (67 patients and 70 controls) of -646G/A, -806C/T, -863C/A, and one study (525 patients and 500 controls) of ?448G/A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the results of literature search and selection. A total of 186 articles were retrieved with the comprehensive literature search, and finally 25 articles (Bai and Cheng 2004;Balding et al 2004;Lee et al 2004;Um and Kim 2004;Karahan et al 2005;Rubattu et al 2005;Harcos et al 2006;Lalouschek et al 2006;Llamas Sillero et al 2007;Zhang et al 2007;Liu et al 2009Liu et al , 2012Shi et al 2009;Kim et al 2010;Tong et al 2010;Markoula et al 2011;Munshi et al 2011;Sultana et al 2011;Szabo and Acsady 2011;Wu et al 2011;Cui et al 2012;Tuttolomondo et al 2012;Gelfand et al 2013;Ma 2012) (18 in English and seven in Chinese) of them were included in the present study according to the eligible criteria. Forty-nine eligible case-control studies from these 25 articles involve 23 studies of -308G/A (6220 patients and 6531 controls), 14 studies of -238G/A (4760 patients and 4389 controls), four studies of -857C/T (2589 patients and 2097 controls), three studies of -1031T/C (2416 patients and 1948 controls), one study (404 patients and 415 controls) of -244G/ A and -367G/A, one study (67 patients and 70 controls) of -646G/A, -806C/T, -863C/A, and one study (525 patients and 500 controls) of ?448G/A.…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al 2010;Sultana et al 2011;Szabo and Acsady 2011;Cui et al 2012;Tuttolomondo et al 2012;Gelfand et al 2013;Ma 2012) reported G allele frequencies, with 13 studies of Asian adults, one of Asian children, seven of Caucasian adults, and two of Caucasian children.…”
mentioning
confidence: 99%
“…1. Finally, eight case-control studies were included in the meta-analysis with a total number of 426 paediatric patients with AIS and 778 control subjects [12][13][14][20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Caucasians were the most common race. In order to genotype the MTHFR 1298A>C polymorphism, PCR-RFLP analysis was used in four of the studies [12,13,20,21], CVD StripAssays in two studies [14,22] and Taqman PCR in one study [23]. The genotyping method was not specified in one of the studies [24].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation